2016
DOI: 10.1103/physreve.94.042601
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ellipsoidal tracers in swimming algal suspensions

Abstract: Enhanced diffusion of passive tracers immersed in active fluids is a universal feature of active fluids and has been extensively studied in recent years. Similar to microrheology for equilibrium complex fluids, the unusual enhanced particle dynamics reveal intrinsic properties of active fluids. Nevertheless, previous studies have shown that the translational dynamics of spherical tracers are qualitatively similar, independent of whether active particles are pushers or pullers-the two fundamental classes of act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
1
24
0
2
Order By: Relevance
“…Pair-correlations are also crucially dependent on the swimming mechanism (pusher vis-á-vis puller), and lead to larger velocity variance and tracer diffusivities in suspensions of pushers (see figures 6 and 12). Thus, in contrast to recent work emphasizing the role of anisotropic tracers (Peng et al 2016;Yang et al 2016), spherical tracers already discriminate between pusher and puller suspensions on account of hydrodynamically induced correlations.…”
Section: Resultsmentioning
confidence: 91%
“…Pair-correlations are also crucially dependent on the swimming mechanism (pusher vis-á-vis puller), and lead to larger velocity variance and tracer diffusivities in suspensions of pushers (see figures 6 and 12). Thus, in contrast to recent work emphasizing the role of anisotropic tracers (Peng et al 2016;Yang et al 2016), spherical tracers already discriminate between pusher and puller suspensions on account of hydrodynamically induced correlations.…”
Section: Resultsmentioning
confidence: 91%
“…This anomalous coupling and diffusion was attributed to the mechanical properties of swimming microorganisms, being pushers or pullers, and to the corresponding strain generated by the active fluid. 37 We note that dense suspensions of bacteria have a tendency to produce swarming motion. [13][14][15][16][17] This swarming motion of bacteria seems to share some similarities with the behavior of coherent bundles of fluid particles recently reported in laboratory turbulent 2D flows.…”
Section: Discussionmentioning
confidence: 93%
“…Yang et al. validated this prediction using suspensions of the algae C. reinhardtii , and found that the long‐time particle diffusion along the major axis of the ellipsoids became more strongly enhanced as the concentration of the algal cells increased (Figure d) . It was therefore shown that, when the rotational degree of freedom was considered, the swimming mechanism of the active particles directly affected the coupling between the translation and rotation of asymmetric passive tracers.…”
Section: Micronscale Systemsmentioning
confidence: 94%